Expression, purification, crystallization and preliminary X-ray diffraction of a novel Nitrosomonas europaea cytochrome, cytochrome P460 - Elmore, Bradley O. (International Union of Crystallography, 2006)
Cytochrome P460 from Nitrosomonas europaea, a novel mono-heme protein containing an unusual cross-link between a conserved lysine and the porphyrin ring, has been recombinantly expressed and purified from Escherichia coli. The protein crystallizes readily and diffraction to 1.7 Å has been obtained in-house. The crystals belong to the trigonal space group P3(1/2)21, with unit-cell parameters a = b = 53.3, c = 127.1 Å, and contain one monomer in the asymmetric unit.